2023
DOI: 10.1002/advs.202205975
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Electronic Interaction between Atomically Dispersed Fe and RuO2 Attaining High Catalytic Activity and Durability Catalyst for Li‐O2 Battery

Abstract: It is significant to develop catalysts with high catalytic activity and durability to improve the electrochemical performances of lithium‐oxygen batteries (LOBs). While electronic metal‐support interaction (EMSI) between metal atoms and support has shown great potential in catalytic field. Hence, to effectively improve the electrochemical performance of LOBs, atomically dispersed Fe modified RuO2 nanoparticles are designed to be loaded on hierarchical porous carbon shells (FeSA‐RuO2/HPCS) based on EMSI criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…To further probe the surface structure of the a/c-RuO 2 /TiO 2 electrodes, ex situ XPS techniques are further carried out. The high-resolution Li 1s XPS spectra of a/c-RuO 2 /TiO 2 electrodes (Figure b and c) can be deconvoluted into two Li–O vibrations around 56.01 and 55.4 eV, corresponding to amorphous Li 2‑ x O 2 and crystalline Li 2 O 2 , respectively. ,, The proportion of Li 2‑ x O 2 in Li 1s XPS spectra of a-RuO 2 /TiO 2 is higher than that of c-RuO 2 /TiO 2 . Previous studies have shown that the amorphous discharge product (Li 2‑ x O 2 ) decomposes more easily than the crystalline discharged product (Li 2 O 2 ) during the OER process. ,,, As shown in Figure d and e, electrochemical impedance spectroscopy (EIS) was employed to investigate the cathodes at different discharged and charged states.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…To further probe the surface structure of the a/c-RuO 2 /TiO 2 electrodes, ex situ XPS techniques are further carried out. The high-resolution Li 1s XPS spectra of a/c-RuO 2 /TiO 2 electrodes (Figure b and c) can be deconvoluted into two Li–O vibrations around 56.01 and 55.4 eV, corresponding to amorphous Li 2‑ x O 2 and crystalline Li 2 O 2 , respectively. ,, The proportion of Li 2‑ x O 2 in Li 1s XPS spectra of a-RuO 2 /TiO 2 is higher than that of c-RuO 2 /TiO 2 . Previous studies have shown that the amorphous discharge product (Li 2‑ x O 2 ) decomposes more easily than the crystalline discharged product (Li 2 O 2 ) during the OER process. ,,, As shown in Figure d and e, electrochemical impedance spectroscopy (EIS) was employed to investigate the cathodes at different discharged and charged states.…”
Section: Resultsmentioning
confidence: 95%
“…74-0115). In contrast, the discharged a-RuO 2 /TiO 2 shows two weak peaks at 32.8° and 34.9°, indicating the formation of Li 2 O 2 with poor crystallinity. , After the full charging process, the peaks associated with Li 2 O 2 completely disappear in the a-RuO 2 /TiO 2 cathode. By contrast, the related Li 2 O 2 peaks did not disappear fully in the c-RuO 2 /TiO 2 cathode, which is consistent with SEM observation.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that in AC-HAADF-STEM images, the brightness of different species is directly proportional to the square of their relative atomic mass. 42 In Ru SA -MCO, Ru has a larger relative atomic mass compared to Mn and Co, thus appearing as bright spots (highlighted by yellow circles) (Figure 1e−g). The bright spots of Ru atoms are uniformly dispersed on the MCO substrate, indicating the preliminary inference that Ru may exist in the form of single atoms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[3,4] Efficient DOI: 10.1002/adsu.202300510 bifunctional catalytic cathodes are highly desired to facilitate both the ORR and the OER, thereby achieving the high practical energy densities of Li−O 2 batteries. [5] So far, single-component catalytic materials that have intrinsic bifunctional ORR and OER catalytic activities are limited to ruthenium oxides, [6,7] perovskites, [8] etc. To this end, combinatorial strategies integrating the catalytic activities of different components were proposed to prepare more alternative bifunctional catalysts.…”
Section: Introductionmentioning
confidence: 99%